Sex‐Related Differences in the Prognostic Role of Acetylcholine Provocation Testing - Riccardo Rinaldi; Michele Russo; Giovanni Occhipinti; Claudio Laudani; Ilaria Torre; Michele Colucci; Filippo Luca Gurgoglione; Francesco Maria Animati; Jacopo Lenkowicz; Andrada Mihaela Tudor; Giovanna Liuzzo; Tommaso Sanna; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Intracoronary provocation testing with acetylcholine (ACh) is helpful to diagnose and risk‐stratify patients with ischemia with nonobstructed coronary arteries (NOCA) and myocardial infarction with NOCA. This study explored potential sex‐related disparities on the prognostic significance of ACh provocative testing. Methods Consecutive patients with ischemia with NOCA and those with myocardial infarction with NOCA who underwent ACh provocation testing were enrolled. The primary end point was the incidence of major adverse cardiovascular and cerebrovascular events at follow‐up. Co‐primary end points were angina recurrence and quality of life assessed by 12‐month Seattle Angina Questionnaire (SAQ) summary score. Results A total of 519 patients (mean age, 61.4±12.1 years; 275 [53.0%] women and 244 [47%] men) were enrolled: 346 (66.7%) with ischemia with NOCA and 173 (33.3%) with myocardial infarction with NOCA. A positive ACh test was observed in 274 (52.8%) patients, with a lower prevalence of epicardial spasm (82 [56.2%] versus 106 [82.8%]) and a higher prevalence of microvascular spasm (64 [43.8%] versus 22 [17.2%]) in women compared with men (P>0.001). After a median 22‐month follow‐up, major adverse cardiovascular and cerebrovascular events occurred in 53 (10.2%) patients, without significant sex differences (P>0.05). Men with a positive ACh test had a significantly higher rate of major adverse cardiovascular and cerebrovascular events (22 [17.2%] versus 5 [4.3%], P=0.002) compared with those with a negative test; no difference was observed in women (P>0.05) (P for interaction=0.003). Women with a positive test experienced a higher rate of angina recurrence (61 [41.8%] versus 32 [24.8%], P=0.005) and a lower SAQ summary score (82 [interquartile range, 72–90] versus 86 [interquartile range, 78–100], P<0.001) compared with those with a negative result; no difference was observed in men (P>0.05). Conclusions This study revealed the importance of recognizing sex‐specific differences in the prognostic value of ACh testing for proper management of coronary vasomotor disorders.